2022
DOI: 10.3390/jof8070755
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Cultural and Pathogenic Variability of Sclerotinia sclerotiorum Causing White Mold of Common Beans in Temperate Climate

Abstract: The present systematic research on cultural, morphological, and pathogenic variability was carried out on eighty isolates of Sclerotinia sclerotiorum collected from major common bean production belts of North Kashmir. The isolates were found to vary in both cultural and morphological characteristics such as colony color and type, colony diameter, number of days for sclerotia initiation, sclerotia number per plate, sclerotial weight, and size. The colony color ranged between white and off-white with the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Assessment of isolate lesion formation on sunflower stems revealed a broad range of aggressiveness among the studied isolates and identified isolates that were highly aggressive on one or both sunflower inbred lines used for evaluations. Variation in S. sclerotiorum isolate aggressiveness has been reported previously on numerous crop hosts, including sunflower ( Ekins et al, 2007 ; Otto-Hanson et al, 2011 ; Taylor et al, 2015 ; Denton-Giles et al, 2018 ; Yu et al, 2020 ; Rather et al, 2022 ). We observed only a modest correlation between isolate aggressiveness on the two sunflower inbred lines, consistent with observations of genotype-isolate interactions for S. sclerotiorum isolates evaluated on crop hosts such as soybean, canola, and sunflower ( Davar et al, 2011 ; Ge et al, 2012 ; Willbur et al, 2017 ; Buchwaldt et al, 2022 ).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Assessment of isolate lesion formation on sunflower stems revealed a broad range of aggressiveness among the studied isolates and identified isolates that were highly aggressive on one or both sunflower inbred lines used for evaluations. Variation in S. sclerotiorum isolate aggressiveness has been reported previously on numerous crop hosts, including sunflower ( Ekins et al, 2007 ; Otto-Hanson et al, 2011 ; Taylor et al, 2015 ; Denton-Giles et al, 2018 ; Yu et al, 2020 ; Rather et al, 2022 ). We observed only a modest correlation between isolate aggressiveness on the two sunflower inbred lines, consistent with observations of genotype-isolate interactions for S. sclerotiorum isolates evaluated on crop hosts such as soybean, canola, and sunflower ( Davar et al, 2011 ; Ge et al, 2012 ; Willbur et al, 2017 ; Buchwaldt et al, 2022 ).…”
Section: Discussionmentioning
confidence: 53%
“…Isolates of S. sclerotiorum have been reported to vary considerably in numerous traits related to growth and development as well as pathogenicity. This includes variation in rates of in vitro hyphal growth, pigmentation of mycelia, size and number of sclerotia formed, and aggressiveness in causing lesions on host plants ( Otto-Hanson et al, 2011 ; Attanayake et al, 2012 ; Rather et al, 2022 ). Consequently, a comprehensive understanding of isolate diversity for this pathogen is important to facilitate resistance breeding efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the disease can involve all parts of the plant, with acropetal development. During the infection, lesions occur on the petioles, branches, and stem, with the final evasion of gray mycelium on all of the organs involved [ 114 ]. In the advanced stages of the disease, the pods appear discolored and are characterized by soft rot.…”
Section: Seedborne Fungi and Oomycetes Of Principal Leguminous Cropsmentioning
confidence: 99%
“…In the former, sclerotia germinate, generating apothecia and ascospores that infect the aerial portions of host plants, while, in the second case, sclerotia produce hyphae that can directly infect the tissues. In legumes, the mycelium develops an appressorium able to directly use enzymes or produce mechanical force to penetrate through the stomata [ 114 ]. White mold has been reported as a seedborne pest for common bean and soybean, producing issues in the germination stage.…”
Section: Seedborne Fungi and Oomycetes Of Principal Leguminous Cropsmentioning
confidence: 99%
“…Additionally, a study showed a positive correlation between sclerotinia virulence and colony diameter, but no correlation was found between virulence and the number, size, or weight of sclerotia. (Rather et al 2022). Consequently, the relationship between the sclerotia formation and virulence of S. sclerotiorum needs to be further investigated.…”
Section: Possible Inhibitory Evidence Regarding the Two Acids On S Sc...mentioning
confidence: 99%